Analysis of flow and baseflow trends in the Usangu Catchment, Tanzania - Shu, Yunqiao; Villholth, Karen G. (2012)
Perceived increased water scarcity in the Usangu catchment, Tanzania has raised social conflict that requires proper water management. Proper management of water resources requires understanding long-term trends of hydrological change. Information of baseflow is critical in the assessment of changes as it is the main contributor to stream flow in the dry season, while also indicating potential shifts in flow pathways in a catchment, including that of groundwater. Three upper perennial tributaries as well as a lower main channel downstream of the Usangu catchment were analysed in this study. The recursive digital filter (RDF) method was used to quantify baseflow with monthly stream flow records. Baseflow decline over the 50-year period (1960-2009) was a generally observed phenomenon across the catchment in all the streams investigated. A significant downward sloping change point was detected in 1989/1990. Total stream flows also decreased for the western part (because baseflow constituted a major share), whereas total stream flows did not change for the eastern and lower section. These phenomena may be partially explained by climate factors (including rainfall and potential evapotranspiration (ET)) as well as human activities (e.g. deforestation, irrigation, and groundwater abstraction) taking place in the lower as well as upper parts of the catchment.